STRATEGIES FOR ENHANCING TRANSFORMATIONAL LEADERSHIP IN THE DIGITAL AGE OF FUJIAN UNIVERSITY OF TECHNOLOGY IN FUJIAN PROVINCE PEOPLE'S REPUBLIC OF CHINA - Reangerng, Gang; Kawsrimol, Buranajit; Suteeniran, Niran; Dechome, Pachara; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2023)
The purpose of this research is 1) To study the transformational leadership in the digital age of Fujian University of Technology in Fujian Province. People's Republic of China 2) To assess the strategic characteristics of transformative leadership in the digital age of universities of technology. Fujian in Fujian Province People's Republic of China 3) To study the strategy of fostering transformational leadership in the digital era of Fujian University of Technology in Fujian Province. People's Republic of China in 4 aspects, consisting of 1) the aspect of having an ideological influence 2) aspects to inspire 3) Aspects to stimulate intellectual 4) The aspect that will take into account the individuality of the research population is Fujian University of Technology in Fujian Province, People's Republic of China. The samples used in this study were administrators and lecturers at Fujian University of Technology in Fujian Province. People's Republic of China By random sampling, there were 226 people in total. The results showed that Strategies for Enhancing Transformational Leadership in the Digital Age of Fujian University of Technology in Fujian Province People's Republic of China, overall, all 4 aspects were at a high level when considering each aspect. had the highest mean, followed by the aspect of ideological influence. As for the aspect that takes into account the individual has the lowest average. The management of an excellent organization requires visionary leaders. Aware of changes in the context of the future global society, there is a systematic and quality action plan that covers indicators.